MENINGKATKAN PEMBELAJARAN LOMPAT JAUH MELALUI PERMAINAN LOMPAT KATAK PADA SISWA KELAS V SD NEGERI 01 REMBUN KECAMATAN SIWALAN KABUPATEN PEKALONGAN TAHUN AJARAN 2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
Based on observations of  the learning process at hletics, especiall y the long jump at the f if t h grade students of SDNegeri 01  Rembun  Siwalan  Pekalongan district  has not  gone wel l, because  st udents are l ess chance of   mot ion.From  the  descript i on  of   t he  probl em,  the  authors  strive  to  increase  learning  outcomes  long  jump  t hrough  aleapfrog  game  that   aims  to  apply  the  concept   of  motion  long  j ump  through  a  leapfrog  game  to  add  t o  themot ion  activit y  of  student s.  So  as  to  foster  a  sense  of   excitement  and  improve  student  l earning  outcomes  longj ump. This type of research is a classroom action research using practice tests. Subj ects were fifth grade st udentsof   SD  Negeri  01  Rembun  who  are  32  student s.  Inst ruments  used  observation  and  observation  test s.  Dataanalysi s techniques used in this study is   t he comparative descriptive  stat i stics.Conclusions  based  on  the  result s  of  action  research,  l earning  through  play  l eapfrog  approach,  can  improvelearning  outcomes  long  j ump.  From  the  anal ysis  of  t he  first  cycl e  is  known  percent age  of  53.13%  mast erylearning st udent number 17, in the second  cycl e  increased by 75%,  wit h  t he number  of 24  student   mastery.